2014
DOI: 10.1177/0731684414537360
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofiber breakage in composite processing using a capillary rheometer

Abstract: This study used a capillary rheometer to determine the impact that shear and elongational flow have on the breakage of aspen fibers in a polypropylene matrix. Composites were processed at different concentrations, temperatures, and rates of strain. The influence of the processing parameters was also analyzed. The difference in breakage of the fibers was assessed through their weight–average fiber length. Results showed that both types of flow exert influence on the total breakage of the fibers. In some cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Based on the works by Goris et al, 8 Quijano-Solis et al 10 and Moritzer et al 9 we concluded that fibre loading plays a significant role in the FB process. In future works, we will use CRIM to isolate the effect of fibre loading on FB designing the test temperature so as to match the same viscosity for each composite.…”
Section: Future Workmentioning
confidence: 73%
See 3 more Smart Citations
“…Based on the works by Goris et al, 8 Quijano-Solis et al 10 and Moritzer et al 9 we concluded that fibre loading plays a significant role in the FB process. In future works, we will use CRIM to isolate the effect of fibre loading on FB designing the test temperature so as to match the same viscosity for each composite.…”
Section: Future Workmentioning
confidence: 73%
“…In this work, the composite materials used for all tests of Table 3 had the same fibre loading, so we also neglected variations in the effect of fibre–fibre interactions on FB for the different test conditions. Goris et al, 8 Quijano-Solis et al 10 and Moritzer et al 9 studied the effect of fibre loading on FB using Couette and capillary rheometers. They found increased FB as a function of fibre loading, but the effect was less notorious for fibre contents higher than 30 wt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the loss in aspect ratio values was less pronounced in smaller fibres (1.5 mm in length and 36 µm in width) than for larger fibres (1.7 mm in length and 48 µm in width) after processing with PP in a Brabender mixer. The authors extended the study to the effect of processing conditions and found that higher extrusion temperature, faster screw speed and higher wood content are conducive to more fibre breakage [Quijano-Solis & Yan, 2014]. The high shear forces from faster screw speed and the higher chance of additional breakage through rough fibre-fibre contacts from higher wood content were suggested to explain the observed more severe fibre breakage.…”
Section: Fibre Breakagementioning
confidence: 98%